ORTHO-PERIODONTAL INTERRELATIONSHIP. A REVIEW - Ioana-Andreea Sioustis; Maria-Alexandra Martu; Odette Luca; Diana-Cristala N; Ionut Luchian; Anamaria Zaharescu; Bogdan Vasiliu; Ioana Rudnic; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2019)
The interrelation between orthodontics and periodontics is evident. In daily practice is common to meet patients with periodontal disease associated with dental malpositions. In addition, it is also common to observe dental migrations secondary to periodontal disease. In this context, the dentist may have to question the possibility and the necessity of orthodontic treatment. The question is if orthodontic treatment improves the existing periodontal situation and if is possible to perform orthodontic treatment on a reduced periodontium without causing other complications. This review highlights three most important periodontal complications of the orthodontic treatment and it assesses the necessity of the periodical periodontal controls and treatments before, during and after the orthodontic treatment.